Dual income taxation : why and how? - Peter Birch Sørensen (Center for Economic Studies and ifo Institute (CESifo), 2005)
The dual income tax combines a progressive tax schedule for labour income with a low flat tax rate on capital income and corporate income. This paper restates the case for the dual income tax and discusses alternative methods of taxing business income under such a tax system, paying special attention to the taxation of income from closely held corporations. It is argued that the imputed normal return to shares in unlisted companies should be taxed as capital income, while above-normal returns should be subject to labour income tax. The paper demonstrates that such a tax scheme can be designed to be neutral towards the firm's investment and financing decisions and towards the decisions of shareholders to realize their shares.
Keywords: H25; H24; 330; dual income tax; tax neutrality; taxation of business income; shareholder income tax; Duale Einkommensteuer; Besteuerungsgrundsatz; Körperschaftsteuer; Flat Tax; Einkommensteuer; Steuerprogression; Theorie; Nordeuropa